New records of Chaetoceros Ehrenberg from wetlands of Cox’s Bazar, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2023)
Eleven species of marine Chaetoceros Ehrenberg newly recorded from Bangladesh have been illustrated and described in the present paper. The species are: Chaetoceros aequatorialis Cleve, C. constrictus Gran, C. decipiens Cleve, C. denicus Cleve,  C. didymus Ehrenberg, C. diversus Cleve, C. pelagicus Cleve, C. pendulus Karsten, C. pseudobrevis Pavillard, C. seychellarus G.H.H. Karsten and  C. tetrastichon Cleve. All of these species have been described here with citation of relevant references and collections examined.Bangladesh J. Plant Taxon. 30(1): 37-41, 2023 (June)